Characterization of early gene transcripts of molluscum contagiosum virus - Bugert, Joachim J.; Lohmüller, Claudia; Darai, Gholamreza (Virology, 1999)
Molluscum contagiosum virus (MCV), a member of the family Poxviridae, replicates well in vivo but cannot be propagated in cell culture. The coding capacity of the MCV genome was previously determined by DNA nucleotide sequence analysis. The objective of the present study was to establish experimental systems for the identification and characterization of early MCV gene transcripts. MCV mRNA was obtained in three ways: (1) MCV early mRNA was synthesized in vitro using permeabilized virions, (2) MCV mRNA was extracted from MCV-infected skin tissue, and (3) MCV mRNA was extracted from MCV-infected human embryonic fibroblasts. RNA/DNA hybridization experiments showed significant early transcriptional activity in two parts of the MCV genome. Transcripts of 11 early MCV genes located in these parts of the genome, including two subunits of the MCV DNA-dependent RNA polymerase (mc077R and mc079R), the MCV poly(A)+ polymerase gene (mc076R), and the MCV MHC class I homolog (mc080R), were detected in reverse transcription-polymerase chain reaction experiments. Total RNA obtained from MCV-infected skin tissue was used to confirm these results. Three MCV early transcripts, mc002L, mc004.1L, and mc005L, produced distinct bands on rapid amplification of their 3' ends (3' RACE). The 5' mapping of transcription start sites of MCV open reading frames (ORFs) mc002L, mc004.1L, mc005L, and mc148R revealed that the MCV RNA polymerase transcription start sites are consistently located between 11 and 13 nucleotides downstream of the early MCV consensus promoter signal. When cDNA from both 5' and 3' mapping experiments was analyzed, MCV ORFs mc004. 1L and mc005L were found to be transcribed as a single bicistronic mRNA. The transcript from MCV ORF mc066L, encoding a glutathione peroxidase, was detected in in vitro synthesized MCV mRNA as well as in total RNA from MCV-infected human embryonic fibroblasts and MCV-infected skin. This indicates that despite the lack of an early MCV consensus promoter signal immediately proximal to the start codon, this particular gene is transcribed early during MCV infection.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 19.03.2021